Car Robots of Line Followers and False Detections Using Microcontroller of BS2SX Basics Tamp - Sujarwata, Sujarwata (Journal Of Natural Sciences And Mathematics Research, 2017)
This study aims to design a robot car that can follow the line and can avoid obstacles if it detects objects. The movement of the robot car is equipped with light sensor (LDR) and ultrasonic as its navigation system. Automation system navigation settings using BS2SX Basic Stamp microcontroller hardware, while the software with Pbasic programming language. The program is written on the Basic Stamp Editor already installed on the PC, then downloaded to EEPROM. Ultrasonic sensors are utilized as a detection of obstacles and light sensor sensors (LDR) as a tracked line detector. The robot will follow the designed line, if there are obstacles in front of it the robot will avoid and run back if the ultrasonic sensor does not detect obstacles in front of it. With the PWM signal input setting (Pulse Width Modulation) from the microcontroller, the robot car can walk straight, turn and will avoid when detecting obstacles. Â©2017 JNSMR UIN Walisongo. All rights reserved